The relationship between personality traits and susceptibility to social influence. - Oyibo, Kiemute; Vassileva, Julita (Computers in Human Behavior, 2019)
Research has shown that social influence can be leveraged as a persuasive strategy to elicit beneficial behaviors, especially if it is tailored to the target audience. However, research on the impact of personality traits on users' susceptibility to social influence is scarce. To bridge this gap, using a sample of 350 participants, we investigate: (1) the personality-based determinants of users' susceptibility to three social influence strategies—Social Learning, Social Proof and Social Comparison—which are currently being employed in persuasive applications to motivate users to engage in beneficial behaviors; and (2) the moderating effect of gender. Our results reveal that Neuroticism is the most consistent determinant of users' susceptibility to social influence, followed by Openness and Conscientiousness. Specifically, we found that: (1) individuals who are high in Neuroticism are more likely to be susceptible to all three social influence strategies than individuals who are low in Neuroticism ; (2) individuals who are low in Openness are more likely to be susceptible to Social Proof and Social Comparison than individuals who are high in Openness ; and (3) individuals who are low in Conscientiousness are more likely to be susceptible to Social Learning and Social Poof than individuals who are high in Conscientiousness. Finally, based on our findings, we provide a number of design guidelines for personalizing persuasive applications to users who are high in Neuroticism , low in Conscientiousness and/or low in Openness. • Users who are high in Neuroticism are more likely to be susceptible to Social Learning, Social Proof and Social Comparison. • Users who are low in Openness are more likely to be susceptible to Social Proof and Social Comparison. • Users who are low in Conscientiousness are more likely to be susceptible to Social Learning and Social Poof. • The relationships between Neuroticism / Openness / Conscientiousness and the three social influence strategies cut across gender.